Does Body Mass Index Impact Outcomes in Patients Undergoing Minimally Invasive Mitral Valve Surgery? - Mariafrancesca Fiorentino; Elisa Mikus; Diego Sangiorgi; Alberto Tripodi; Simone Calvi; Elena Tenti; Antonino Costantino; Carlo Savini (Medicina)
Background: This study examines the impact of Body Mass Index (BMI) on outcomes after mitral valve surgery via right minithoracotomy, an approach that may reduce wound complications in obese patients. Methods: Between January 2010 and December 2024, 1773 adult patients underwent minimally invasive mitral valve surgery at our institution. They were categorized into three groups: normal weight (BMI < 25, n = 942), overweight (BMI 25–30, n = 661), and obese (BMI > 30, n = 170). Results: The three groups exhibited significant differences, with a higher prevalence of hypertension, dyslipidemia, and diabetes (p < 0.001) in overweight and obese patients. Further-more, they had a greater incidence of preoperative atrial fibrillation (p < 0.001), prior stroke (p = 0.023), chronic obstructive pulmonary disease (p = 0.002), and elevated preoperative creatinine levels (p < 0.001). and their euroscore II was significantly higher (p = 0.040). In-hospital mortality and major complications were similar across groups, except for drainage output in the first 24 h (p = 0.002) and ICU stay (p = 0.022), both resulting higher in the overweight and obese patients. We employed inverse probability of treatment weighting (IPTW) to create three well-matched groups. Following IPTW, postoperative outcomes remained comparable across groups. However, obese patients exhibited a higher incidence of postoperative atrial fibrillation (p = 0.037) and required pacemaker implantation more frequently (p < 0.001). Conclusions: Our findings suggest that obesity does not increase the risk of mortality or major adverse events after minimally in-vasive mitral valve surgery. This approach may offer a less invasive alternative for obese patients, potentially reducing the risk of wound complications associated with conventional surgery.